COVID-19 Pandemic: Impact of Agricultural Labour Migration on Income Levels of Farmers in Telangana - Muneer, Shaik; Swamy, D. Kumara; Lavanya, T.; Supriya, K. (International Journal of Bio-resource and Stress Management, 2023)
The present study was undertaken during 25th March 2019 to 25th March 2021 to examine the impact of agricultural labour migration due to COVID-19 pandemic on the income levels of farmers. Both primary and secondary data were used in the study, multistage sampling technique was used in selection of district, mandals and villages. Tools and techniques like tabular analysis, gross returns and net returns were used. Economic impact on farmers in the study area was studied by selecting three major crops viz., Paddy, Cotton and Maize. During the COVID-19 pandemic, in the kharif and rabi season, in all the three major crops, the labour availability was increased when compared with the period of before the pandemic. This situation was appeared due to reverse migration during pandemic. The average wage rates received by the agricultural labourers for almost all farm operations in case of paddy, maize and cotton crops were decreased due to increase in labour supply due to reverse migration. The available man days also clearly got increased for almost all the operations except harvesting of paddy and cotton crops. In case of paddy and cotton crops, net returns were found to increase. In case of Maize crop, the gross and net returns were decreased due to increase in total operation costs and decrease in price per quintal during rabi season of the pandemic period respectively.